Finding Sunshine on a Cloudy Day: A Positive Affect Intervention for Co-Occurring Methamphetamine Use and HIV. Issue 2 (May 2022) - Olem, David; Earle, Maya; Gómez, Walter; Coffin, Lara; Cotten, Paul; Jain, Jennifer P.; Moskowitz, Judith T.; Carrico, Adam W.
Highlights: Describes a novel positive affect intervention to improve long-term outcomes. Details the theoretical underpinnings of the positive affect intervention. Provides a case study example of how the positive affect intervention is tailored. Underscores the complex care needs of sexual minority men who use methamphetamine. Abstract: Among sexual minority men (i.e., gay, bisexual, and other men who have sex with men) living with HIV, those who use methamphetamine experience profound health disparities. Affect Regulation Treatment to Enhance Methamphetamine Intervention Success (ARTEMIS) is an evidence-based, 5-session, individually delivered positive affect intervention adapted for sexual minority men living with HIV who use methamphetamine. ARTEMIS was designed to amplify the benefits of evidence-based substance use interventions such as contingency management (CM) with this high-priority population. Delivering ARTEMIS during CM has been shown to assist participants in reducing stimulant use, increasing positive affect, and achieving durable reductions in HIV viral load. We describe the theoretical underpinnings of the ARTEMIS intervention, provide details of the training and session protocols with a case example, and discuss implications for future applications in research and clinical settings.